Heterogeneously Catalysed Hydroamination. Issue 4 (1st December 2020) - Sengupta, Manideepa; Das, Subhasis; Islam, Sk. Manirul; Bordoloi, Ankur
Abstract: The direct addition of amines to alkynes and olefins is an elegant approach for C−N bond formation in contrast to other conventional synthetic organic methods that afford higher substituted amines; comprising essential organo‐nitrogen compounds which are the scaffolds present in important N‐heterocycles. Heterogeneous catalyzed direct amination is presented in this Review, along with the advantages, the structure‐activity relationship of applied solid acids, functionalized nanomaterials and heterogeneous single metal site catalysts that play a pivotal role towards tuning the formation of branched and linear amines. Abstract : Heterogeneously catalyzed hydroamination : This Review focuses on the advances in the field of heterogeneously catalyzed hydroamination since the last three decades. The structure‐activity relationship of the solid acids, the functionalized nanomaterials and the single metal site catalysts have been discussed towards the C−N bond formation reaction via the most atom economic direct addition of N−H nucleophiles to multiple C−C bonds.